ISH BILAN BANDLIK VA IQTISODIY RIVOJLANISH: STATISTIK TAHLIL (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This scientific article is devoted to the statistical analysis of the employment rate and its impact on economic development processes. The labor market is an important component of the economy of any state, and its stability and efficiency are one of the main factors of economic growth. The unemployment rate, the distribution of employment by sector, the employment of youth and women, and how labor productivity affect the economic development process are scientifically and statistically analyzed.